2022
DOI: 10.3390/jcm11113161
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral Body Tethering in 49 Adolescent Patients after Peak Height Velocity for the Treatment of Idiopathic Scoliosis: 2–5 Year Follow-Up

Abstract: Vertebral Body Tethering (VBT) is a non-fusion surgical treatment for Adolescent Idiopathic Scoliosis (AIS) that elicits correction via growth modulation in skeletally immature patients. VBT after peak height velocity is controversial and is the subject of this study. A retrospective review of Risser 3–5 AIS patients treated with VBT, and min. 2-year FU was performed. Pre to post-op changes in clinical outcomes were compared using Student’s t-test or the Mann-Whitney test. A total of 49 patients met criteria, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 26 publications
2
17
0
Order By: Relevance
“…Hegde et al reported on 10 female skeletally mature patients (Risser 4 and Sanders 7) after minimum 1-year follow-up and reported improvement in Cobb's angle from 52° to 15.9°. In skeletally mature patients, VBT is thought to improve the deformity when maximal intraoperative correction is done because growth potential is limited and thus less predictable growth-guided modulation ( 8 , 15 ). Miyanji et al published on 55 immature patients Risser 0.5 showing clinical success in 77% and 8% insufficient correction requiring conversion to PSF ( 19 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Hegde et al reported on 10 female skeletally mature patients (Risser 4 and Sanders 7) after minimum 1-year follow-up and reported improvement in Cobb's angle from 52° to 15.9°. In skeletally mature patients, VBT is thought to improve the deformity when maximal intraoperative correction is done because growth potential is limited and thus less predictable growth-guided modulation ( 8 , 15 ). Miyanji et al published on 55 immature patients Risser 0.5 showing clinical success in 77% and 8% insufficient correction requiring conversion to PSF ( 19 ).…”
Section: Resultsmentioning
confidence: 99%
“…Miyanji et al published on 55 immature patients Risser 0.5 showing clinical success in 77% and 8% insufficient correction requiring conversion to PSF ( 19 ). Alanay et al reported on mature cohort of Sanders score 6–7 with 100% success, 55% correction and residual curve (9°–27°) at 20 months and Meyers et al reported on 49 mature patients with 76% success, 41% tether breakage and 2% revision with PSF at 32.5 months ( 8 , 26 ). Figures 4 – 6 showcase a 14-year-old female (Sanders 7) that underwent T12-L4 anterior tethering with correction of the curve from 42° to 17° postoperatively and the patient being well balanced at 6-months post surgery.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3 Tether breakage is one of the most common occurrences of AVBT, 4 but the reported incidence varies significantly between studies from 3.3% to 52%. 1,[5][6][7][8][9][10][11][12] The tether tends to fail between levels 3 and failure can be identified radiographically. [1][2][3][6][7][8]11,[13][14][15] An example of a patient with suspected tether breakage is shown in Fig.…”
mentioning
confidence: 99%